The Evolution of Economic Relations Between the USA and Canada: The Interdependence of the Two Economies - A. D. Filina; G. V. Tretyakova (Мир новой экономики, 2022)
The paper presents the results of the study of the evolution of economic relations between the United States and Canada, since 1989. The agreements regulating the economic relations of these countries among themselves and with other trading partners. An economic and statistical study of Canada’s exports to Latin America and the Caribbean and imports from them was carried out. Both Canada and the United States have become leaders in creating an open and free space based on the principles of multilateral trade. The main characteristics of the free trade zone are mutual concessions in terms of access to markets for services and goods; discipline in terms of trade restrictions; the use of dispute settlement mechanisms. Nevertheless, some researchers question the effectiveness of this trading system. US President Joe Biden promises to take measures to intensify bilateral cooperation, but Canadians are concerned about his decision to cancel the Keystone XL pipeline project. The commitment of the American president to the policy of “buying American” also causes some unrest. The above determines the relevance of considering the issue related to economic cooperation between the United States and Canada in modern conditions. The following research methods were used in the work: the normative method and the method of political analysis.